Booktoks and fiction reading in the digital society: perspectives for critical language education - Azzari, Eliane Fernandes; Zullo , Arthur Henrique Rodrigues (The ESPecialist, 2025)
Considering the “Booktok” phenomenon – TikTok media profiles intended to discuss and/or recommend books –, we expand our discussion of sociocultural events that show interrelationships between practices in the writing society and the digital society. Supported by the digital ethnographic approach and adopting a qualitative perspective, we examined and compared three profiles of Brazilian booktokers: @leticia_biblio; @livraneios and @biapaludetto. Our research shows that – to promote printed books – the three influencers benefited from the speed of engagement that the media’s algorithms offer thus consolidating the confluence between the digital and analogue universes. In view of this, adopting a dialogical and critical approach to linguistic education, we propose to reflect upon the contributions of such results to teacher education, considering that our data indicate that there is still a significant interest, among a portion of the young Brazilians, in fiction texts.